Impacto económico de la violencia armada sobre la producción campesina, caso municipios zona de distensión departamento del Meta, Colombia (1991-2014) (2016)
In the paper, the effects of the armed conflict generated in the rural family productive activity in the municipalities of the demilitarized zone in the department of Meta in the period 1991-2014 are analyzed. This requires a data collection rural family farm production, displacement rates, homicides, massacres and kidnappings carried out in the context of the armed conflict in the municipalities object of this study was ahead. Data that formed the basis for the formulation of an econometric model based on the neoclassical theory of the peasant economy and the liberal sociological theory of armed conflict; which allowed to consolidate a modern analysis of Colombian peasant economy in the twenty-first century. Definitely the armed conflict is presented as a determining factor in the development of the rural family farm production in the municipalities of southwestern department of Meta, since that territory has historically housed, groups outside the law, which added to a limited state presence maintained own dynamics of the conflict (displacement, massacres, kidnappings and killings), which are likely to be addressed through reading this study.